Dinamika Abnormal Return Saham pada Perusahaan Terdaftar di BEI - Ganisya Kirana (UIN Raden Mas Said Surakarta, 2018)
Abstrak The purpose of this research was to get empirical evidence about the effect of the issuance of islamic bonds (sukuk) and conventional bonds on the abnormal stock returns. The independent variables used are islamic bonds (sukuk) and conventional bonds. The dependent variable used in this study is the abnormal stock return in observations from 2008-2016. The population in this study are all issue islamic bonds (sukuk) and conventional bonds on the Indonesia stock exchange, those are 13 companies with criterias issuing islamic bond (sukuk) and conventional bonds, this obtained 30 samples used in this study. And the samples are the compaines listed during the period 2008-2014. The sampling is done by purposive sampling. The result showed based on multiple regression test for islmaic bonds (sukuk) and conventional bonds that positive affect the abnormal stock return Keywords: Islamic bonds (sukuk) conventional bonds, and abnormal stock returns.